'Huis Scharlaken' (Scharlaken House) (Bulletin KNOB, 1994)
In 1986/87 Scharlaken House was excavated by the 'Rijksdienst voor het Oudheidkundig Bodemonderzoek / ROB' (State Service for Archaeological Investigations). The excavation was part of a large and lengthy town-archaeological research in the town centre of Dordrecht. The house was situated along Wijnstraat, which is the westward one of the two old main streets on either side of the central Voorstraatshaven along which the medieval town originated.From the excavation it became evident that the house in its oldest phase was built around 1225. It was a very large brick building (9 x 35 ms), in its essential form comparable to the well-known 'town castles' in Utrecht. It consisted of a large sized front room and a smaller back room. These were connected by three passageways in the dividing wall. The house was accessible from the street and it had an exit in the middle of the rear side. Along the walls of both rooms there was a continuous row of light niches. There were no fire places. Even during its construction, the house had started to subside backwards, into the soft peat behind the main street. This made various constructive adjustments necessary. Original elements, such as the three passageways and the light niches could no longer be used. The floor had to be raised and levelled constantly. In the front room two wooden posts were placed to support the evidently changed storey.The function of building phase 1 has been related to the cloth trade, for which Dordrecht was known since 1200. In the 13th and 14th centuries, the cloth trade developed greatly. However, cloth production never seems to have really got off the ground. Attempts to turn Dordrecht into the centre of the cloth trade as well as of cloth industry and English wool import for the entire delta of the large rivers - to the detriment of Flanders - have never succeeded.In Dordrecht three consecutive halls for the cloth trade are known, although with some intervals of time in between. The latest (approximately 1650-1750) was situated in a former dock tower. The one from the middle period was built as Clothtraders' Hall right across the Voorstraatshaven (from after 1383 until 1544, when the Town Hall was established in this building). It is likely that the oldest Clothtraders' Hall coincided with building phase l of Scharlaken House (dated approximately 1225-1360). The name of Scharlaken does not only refer to colour and/or quality of cloth, but it is also a topographical indication (among other things, a house name) and moreover it also occurs as a family name. All three denotations are to be found in Dordrecht.In Utrecht there was also a Scharlaken House of which it has become evident that the Clothtraders' Hall was established there in the 13th and 14th centuries. In view of the name and furnishing of the ground floor it is quite probable that Scharlaken House in Dordrecht was originally built as a Clothtraders' Hall. The arrangement of the light niches may reflect the places of the market stalls of the traders. A contemporary parallel is provided by instructions for the old Clothtraders' Hall in Bruges. Such early Clothtraders' Halls are rare. Most Halls in The Netherlands are of a later date. The Halls in Leyden.Delft and Bois-le-Duc are known from written sources. Archaeological data are even scarcer; apart from Dordrecht there are partial data from Beverwijk and Utrecht. In the 14th and 15th centuries Clothtraders' Halls of a new, open type were built everywhere in The Netherlands, e.g. in Ghent. The Scharlaken House in Dordrecht was pulled down to ground level around 1360. It was immediately rebuilt as a private dwelling (building phase 2). Due to the formation of a building-line along the street, the front had to be receded. The back room was not rebuilt either, so that the house became considerably shorter in size (18.5 metres). At the back of the premises, a heavy tower was erected with a huge cesspit in the cellar. Thus a type of large late-medieval dwelling was created which, on the basis of excavations elsewhere in the town, can be called exemplary for Dordrecht.Scharlaken House 2 also seems to have played a part in the nobility disputes between ‘Hoeken’ and ‘Kabeljauwen’ when between 1361 and 1388 it was in the possession of lord Otto van Arkel. In the 15th century the house was inhabited by the Scharlaken family. In 1584 the ground floor was furnished as a weighhouse by the town. This latter function has not left any traces from an archaeological point of view. During recent inner-city redevelopment the house was pulled down shortly after 1960. After the archaeological research, the cellar tower of Scharlaken House 2 has been integrated in the modern new development as a historical monument.